Neonatal appendicitis: a survival case study - Izabela Linha Secco; Taine Costa; Etiene Letícia Leone de Moraes; Márcia Helena de Souza Freire; Mitzy Tannia Reichembach Danski; Regina Paula Guimarães Vieira Cavalcante
ABSTRACT Objective: To report a case of neonatal appendicitis in a children's hospital in southern Brazil, demonstrating the impact on neonatal survival. Method: Case study with data collection from medical records, approved by the Institution and Ethics Committee for Research with Human Beings. Results: The clinical picture is initially characterized by food intolerance, evolving to hypoactivity, alteration of vital signs and septicemia due to intestinal perforation. Management is exclusively surgical, since no case described in the literature was diagnosed preoperatively and the findings usually point to acute abdomen. Conclusion: A focused clinical surveillance should be established when the infant presents peritoneal irritation. Follow-up of the evolution and the worsening of the symptoms by nurses, as part of the care team in partnership with the medical team, enables an early surgical intervention, thereby avoiding complications such as septicemia and death.